Xylanase Production From Aspergillus Niger Under Solid State Fermentation Using Different Agro Wastes - Intan Nabihah, Muhammad Suria Sukma (Universiti Malaysia Sarawak (UNIMAS), 2018)
Solid state fermentation technology is used to produce a variety of microbial metabolites such as enzymes. Enzymes are utilized for industrial purposes. This study was focusing on the production of xylanase which is an enzyme that degrades xylan, a hemicellulose found in a plant cell walls into xylose. Xylanase production was obtained from Aspergillus niger via solid state fermentation using various type of agro wastes as substrates such as rice husk, com cob and coconut husk. The enzyme activity was measured by using 1 % birchwood xylan as the substrate and dinitrosalicylic acid method to determine the liberating reducing sugar. In addition, various solid state fermentation variables which are incubation period, incubation temperature and initial moisture content were studied to identify the optimal solid state fermentation conditions for Aspergillus niger to produce xylanase. Based on the results, it was shown that the best substrate producing highest enzyme activity of 0.1064 U was com cob with 70% (v/w) initial moisture content at 30 °C for 6 days.